Auditoria de gestión al departamento de ventas y comercialización y su incidencia en la rentabilidad de la empresa Dipor S.A. del cantón Quevedo año 2014 - Muriel Muñoz, Wilmer Lenin (2015)
This research paper entitled "Auditing the Sales and Marketing Department and its impact on the profitability of Dipor SA in Quevedo canton in year 2014", was based on an audit of the Department of Management Sales and Marketing in order to examine the policies applied to evaluate the system of internal control, management criteria. This paper was carried out through a compendium of interviews and direct observation models made in different business processes. The risk measurements: risk control, confidence level 84.63% high; level of risk 15.37% low risk, the measurement of inherent risk confidence level 72% high, and its inherent risk 28%, so the audit risk is 0.22, indicating that it is low. Management criteria such as efficiency, efficacy and effectiveness demonstrate that there is a 56% of the staff works fulfilling those criteria, while 44% work in the opposite way. As for the profitability criteria, liquidity is 85% and rotation indicator of sales is 5.35%. Having audited the company DIPOR SA the projection was measured according to the policies and procedures of the organization, lack of internal control at the moment of using standards to give recommendations with corrective norms that contribute to the decision making of the company. Keywords: Auditing, internal control, confidence level, level of efficiency, effectiveness level,efficacy level, performance indicators,management indicators.